Negative electrode material, preparation method thereof and lithium ion battery
By using carbon matrix with pores and active substances of silicon particles distributed in the pores in the negative electrode material of lithium-ion batteries, combined with the vapor deposition process, the problem of volume expansion of the negative electrode material during circulation is solved, and its circulation performance and battery service life are improved.
Patent Information
- Application Number
- CN202311426902.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-31
- Publication Date
- 2025-05-02
AI Technical Summary
The negative electrode material of lithium-ion batteries has a severe volume expansion effect during the circulation process, resulting in the material being powdered and broken, and the battery's circulation attenuation is very fast.
Using an active material including a carbon matrix and silicon particles, the carbon matrix has pores, and at least some of the silicon particles are distributed in the pores of the carbon matrix, the silicon particles are fully filled in the pores of the carbon matrix through a vapor deposition process, and the deposition conditions are controlled to reduce the generation of large-sized silicon particles.
Effectively suppress the volume expansion of the negative electrode material, improve its circulation performance, reduce the collapse of the material structure and the side reaction with the electrolyte, and extend the service life of the battery.
Smart Images

Figure CN119920889A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode materials, and in particular to negative electrode materials and preparation methods thereof, and lithium ion batteries. Background Art
[0002] Lithium-ion batteries have the advantages of high energy density, high cycle life, low environmental pollution and no memory effect, so they are widely used in electric vehicles and consumer electronic products. With the rapid development of electric vehicles in recent years, the demand for higher energy density lithium-ion batteries has been growing, which has prompted researchers to look for battery materials with higher energy density and better cycle performance. The positive and negative electrode materials are the core of the battery and determine the working efficiency of the battery. At present, the commercial negative electrode material is graphite, and its capacity is close to the theoretical upper limit, and the further improvement is limited. Therefore, there is an urgent need to develop a new generation of high energy density negative electrode materials. Among them, silicon-based negative electrode materials are generally considered to be the next generation of battery negative electrode materials, with advantages such as high capacity, abundant sources, and relative safety.
[0003] However, the silicon negative electrode has a dramatic volume expansion effect during the cycle, which causes the material to pulverize and break, and the battery cycle decays quickly. There are currently multiple solutions to this problem, including structural design of silicon, the use of nano-, porous and other technical means; improvement by composite coating and other methods; modification and improvement of silicon pole pieces by new electrolytes, adhesives, etc. Among them, nano-sizing is one of the current mainstream directions. Reducing the size of silicon to nano-size can reduce the expansion of silicon and prevent the pulverization of silicon. However, the existing nano-sizing solutions still have many shortcomings in solving the performance of silicon, and there is still a lot of room for improvement in long-cycle performance. Summary of the invention
[0004] The purpose of the present application is to provide a negative electrode material and a preparation method thereof, and a lithium-ion battery, which can effectively inhibit the volume expansion of the negative electrode material and improve the cycle performance of the negative electrode material.
[0005] In a first aspect, the present application provides a negative electrode material, comprising an active material, wherein the active material comprises a carbon matrix and silicon particles, the carbon matrix has pores, and at least part of the silicon particles are distributed in the pores of the carbon matrix;
[0006] A three-electrode battery consisting of a negative electrode prepared from the negative electrode material as a working electrode, metal lithium as a reference electrode, metal lithium as a counter electrode and an electrolyte containing metal lithium ions is charged and discharged to obtain a curve graph showing the relationship between the differential value dQ / dV obtained by differentiating the charge and discharge capacity Q of the potential V of the working electrode with respect to the reference electrode and the potential V of the working electrode;
[0007] In the curve diagram of the relationship between the differential value dQ / dV and the potential V, when the negative electrode material is energized in the direction of delithiation, the differential value dQ / dV when the potential V is between 20mV and 80mV has a maximum peak value A, the differential value dQ / dV when the potential V is between 120mV and 210mV has a maximum peak value B, and B / A≤4.
[0008] In some embodiments, the carbon matrix includes at least one of hard carbon, soft carbon, graphite, mesocarbon microbeads, activated carbon, porous carbon, mesoporous carbon, or carbon gel.
[0009] In some embodiments, the total pore volume of all pores in the carbon matrix is ≥ 0.4 cm 3 / g.
[0010] In some embodiments, the pores in the carbon matrix include micropores, and the volume proportion of the micropores in the total pore volume is ≥ 80%.
[0011] In some embodiments, the average pore size of the pores in the carbon matrix is ≤ 5 nm.
[0012] In some embodiments, the porosity of the carbon matrix is 40% to 60%.
[0013] In some embodiments, the silicon particles include at least one of elemental silicon, silicon oxide, silicon alloy, and silicon-carbon composite.
[0014] In some embodiments, the average particle size of the silicon particles is 1 nm to 500 nm.
[0015] In some embodiments, the mass content of silicon in the silicon particles is ≥ 99%.
[0016] In some embodiments, the negative electrode material further includes a carbon layer located on at least a portion of the surface of the active material, and the carbon layer includes at least one of graphite carbon and amorphous carbon.
[0017] In some embodiments, the median particle size D of the negative electrode material is 50 ≤10μm.
[0018] In some embodiments, the specific surface area of the negative electrode material is ≤5m 2 / g.
[0019] In some embodiments, the pore volume of the negative electrode material is 0.001 cm 3 / g~0.1cm 3 / g.
[0020] In a second aspect, the present application provides a method for preparing a negative electrode material, comprising the following steps:
[0021] providing a carbon matrix having pores;
[0022] The carbon matrix with pores is subjected to vapor deposition using a silicon source gas to obtain an active substance, wherein the negative electrode material includes the active substance, wherein the average pore size of the carbon matrix is D nm, the volume concentration of the silicon source gas is N, the flow rate of the silicon source gas is VL / min, the deposition time of the vapor deposition is th, the deposition temperature of the vapor deposition is T°C, and the deposition relationship is controlled to satisfy: K=(10 3 V 2 ND 3 ) / (t 2 T 1.5 ), 1.1≤K≤6.5.
[0023] In some embodiments, the silicon source gas includes at least one of monosilane, disilane, monochlorosilane, and dichlorosilane.
[0024] In some embodiments, the average pore size of the carbon matrix is 0.1 nm to 20 nm.
[0025] In some embodiments, the volume concentration of the silicon source gas is 1% to 80%.
[0026] In some embodiments, the flow rate of the silicon source gas is 0.5 L / min to 500 L / min.
[0027] In some embodiments, the vapor deposition time is 0.5 h to 20 h.
[0028] In some embodiments, the deposition temperature of the vapor deposition is 300°C to 800°C.
[0029] In some embodiments, the carbon matrix includes at least one of hard carbon, soft carbon, graphite, mesocarbon microbeads, activated carbon, porous carbon, mesoporous carbon, or carbon gel.
[0030] In some embodiments, the pore volume of the carbon matrix is ≥ 0.4 cm 3 / g.
[0031] In some embodiments, the pores in the carbon matrix include micropores, and the proportion of the micropores is ≥ 80%.
[0032] In some embodiments, the average pore size of the pores in the carbon matrix is ≤ 5 nm.
[0033] In some embodiments, the porosity of the carbon matrix is 40% to 60%.
[0034] In some embodiments, the step of providing a carbon matrix having pores comprises: carbonizing a carbon source, and then acid-washing and activating the carbonized product to obtain a carbon matrix having pores.
[0035] In some embodiments, the carbon source includes at least one of fruit shells, starch, coconut shells, rice husks, coal, lignin, sugars, thermoplastic polyurethane, polylactide, polyglycolide, polyaniline, phenolic resin, polyamide, polyacrylonitrile, polychloroprene, polyphosphate, etc.
[0036] In some embodiments, the temperature of the carbonization treatment is 400° C. to 1800° C., and the time of the carbonization treatment is 1 h to 15 h.
[0037] In some embodiments, the step of acid washing the carbonized product comprises placing the carbonized product in an acid solution with a concentration of 1 mol / L to 20 mol / L for 0.5 h to 20 h.
[0038] In some embodiments, the step of pickling the carbonized product includes: placing the carbonized product in an acid solution with a concentration of 1 mol / L to 20 mol / L for 0.5 h to 20 h, wherein the acid solution includes at least one of hydrochloric acid, nitric acid, sulfuric acid, carbonic acid, acetic acid, benzoic acid, hydrofluoric acid, oxalic acid and phosphoric acid.
[0039] In some embodiments, the step of activating the carbonized product includes: drying the acid-washed carbonized product and placing it in a mixed gas of nitrogen and water vapor for activation.
[0040] In some embodiments, the step of activating the carbonized product includes: drying the acid-washed carbonized product and placing it in a mixed gas of nitrogen and water vapor for activation, wherein the volume ratio of the water vapor to the nitrogen is (0.1-20):80.
[0041] In some embodiments, the step of activating the carbonized product includes: drying the carbonized product after acid washing and placing it in a mixed gas of nitrogen and water vapor for activation treatment, the activation treatment temperature is 400°C to 2000°C, and the activation treatment time is 0.5h to 30h.
[0042] In some embodiments, the method further comprises:
[0043] The negative electrode material is subjected to a carbon coating treatment to obtain a negative electrode material having a carbon layer on the surface; the carbon coating treatment includes at least one of solid phase carbon coating, liquid phase carbon coating and gas phase carbon coating.
[0044] In a third aspect, the present application provides a lithium-ion battery, wherein the lithium-ion battery comprises the above-mentioned negative electrode material or the negative electrode material prepared by the above-mentioned negative electrode material preparation method.
[0045] Compared with the prior art, the technical solution of the present application has at least the following beneficial effects:
[0046] The negative electrode material provided in the present application includes an active substance, and the active substance includes a carbon matrix and silicon particles. The carbon matrix has pores, and at least part of the silicon particles are distributed in the pores of the carbon matrix, which can improve the capacity of the negative electrode material. The differential value dQ / dV of the potential V between 20mV and 80mV has a maximum peak value A, and the peak value A can represent the peak intensity formed when the amorphous lithium silicon alloy undergoes a transformation from an amorphous state to a crystalline state under a low lithium insertion potential. The differential value dQ / dV of the potential V between 120mV and 210mV has a maximum peak value B, and the peak value B represents the peak intensity formed when lithium and silicon with a particle size greater than 5nm undergo a lithium insertion process. By controlling the value of B / A within the above range, the present application can reduce the formation of large-sized silicon particles and lithium-silicon alloys in the negative electrode material, thereby ensuring that the negative electrode material can both alleviate volume expansion and maintain structural stability during the cycle, reduce the collapse of the material structure caused by volume expansion during the lithium insertion and extraction process of the negative electrode material, effectively reduce the occurrence of side reactions between the negative electrode material and the electrolyte, and thus improve the cycle performance of the negative electrode material.
[0047] The preparation method of the negative electrode material provided in the present application utilizes a vapor deposition process to fully fill silicon particles in the pores of a carbon matrix to prepare the negative electrode material. By controlling the deposition conditions, the deposition of silicon particles on the surface of the carbon matrix can be reduced, and the silicon particles can be effectively filled in the pores of the carbon matrix to increase the capacity of the negative electrode material. At the same time, the size and shape of the silicon particles can be controlled to ensure that the negative electrode material can both alleviate volume expansion and maintain structural stability during the cycle, reduce the collapse of the material structure caused by volume expansion during the lithium insertion and extraction process of the negative electrode material, effectively reduce the occurrence of side reactions between the negative electrode material and the electrolyte, and thus improve the cycle performance of the negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0049] Figure 1 The V-dQ / dV test curve of the negative electrode material provided in this application;
[0050] Figure 2 This is a scanning electron microscope (SEM) image of the negative electrode material prepared in Example 1 of the present application;
[0051] Figure 3 XRD diagram of the negative electrode material prepared in Example 1 of the present application;
[0052] Figure 4 This is the first charge and discharge curve of the negative electrode material prepared in Example 1 of the present application;
[0053] Figure 5 This is the cycle performance curve of the negative electrode material prepared in Example 1 of the present application. DETAILED DESCRIPTION
[0054] In order to better understand the technical solution of the present invention, the embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0055] It should be clear that the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0056] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0057] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0058] In a first aspect, the present application provides a negative electrode material, comprising an active material, wherein the active material comprises a carbon matrix and silicon particles, the carbon matrix has pores, and at least part of the silicon particles are distributed in the pores of the carbon matrix;
[0059] A three-electrode battery consisting of a negative electrode prepared from the negative electrode material as a working electrode, metal lithium as a reference electrode, metal lithium as a counter electrode and an electrolyte containing metal lithium ions is charged and discharged to obtain a curve graph showing the relationship between the differential value dQ / dV obtained by differentiating the charge and discharge capacity Q of the potential V of the working electrode with respect to the reference electrode and the potential V of the working electrode;
[0060] like Figure 1 As shown in the curve diagram of the relationship between the dQ / dV and the potential V, when the negative electrode material is energized in the delithiation direction, the differential value dQ / dV of the potential V between 20mV and 80mV has a maximum peak value A, the differential value dQ / dV of the potential V between 120mV and 210mV has a maximum peak value B, and B / A≤4.
[0061] The negative electrode material provided in the present application includes an active substance, and the active substance includes a carbon matrix and silicon particles. The carbon matrix has pores, and at least part of the silicon particles are distributed in the pores of the carbon matrix, which can improve the capacity of the negative electrode material. The differential value dQ / dV of the potential V between 20mV and 80mV has a maximum peak value A, and the peak value A can represent the peak intensity formed when the amorphous lithium silicon alloy undergoes a transformation from an amorphous state to a crystalline state under a low lithium insertion potential. The differential value dQ / dV of the potential V between 120mV and 210mV has a maximum peak value B, and the peak value B represents the peak intensity formed when lithium and silicon with a particle size greater than 5nm undergo a lithium insertion process. By controlling the value of B / A within the above range, the present application can reduce the formation of large-sized silicon particles and lithium-silicon alloys in the negative electrode material, thereby ensuring that the negative electrode material can both alleviate volume expansion and maintain structural stability during the cycle, reduce the collapse of the material structure caused by volume expansion during the lithium insertion and extraction process of the negative electrode material, effectively reduce the occurrence of side reactions between the negative electrode material and the electrolyte, and thus improve the cycle performance of the negative electrode material.
[0062] Specifically, the value of B / A can be 4, 3.9, 3.85, 3.42, 3.27, 2.86, 2.65, 2.45, 2.36, 2.27, 1.98, 1.86, 1.59, 1.47, 1.34, 1.22, 1.05, 0.98, 0.54 or 0.37, etc., of course, it can also be other values within the above range, which is not limited here. When the value of B / A is within the above range, the silicon particles are deposited in the pores of the carbon matrix and are small in size, and the proportion of surface silicon and large-particle silicon in the negative electrode material is reduced, which can reduce the volume expansion of the negative electrode material and improve the cycle performance of the negative electrode material.
[0063] In some embodiments, the carbon matrix includes at least one of hard carbon, soft carbon, graphite, mesocarbon microbeads, activated carbon, porous carbon, mesoporous carbon, and carbon gel.
[0064] In some embodiments, the total pore volume of the carbon matrix is ≥ 0.4 cm 3 / g, specifically 0.4cm 3 / g, 0.5cm 3 / g, 0.8cm 3 / g, 1cm 3 / g, 1.1cm 3 / g, 1.3cm 3 / g, 1.5cm 3 / g or 1.8cm 3 / g, etc., and of course, other values within the above range may also be used, which are not limited here. Preferably, the total pore volume of the carbon matrix is ≥0.5cm 3 / g; further preferably, the total pore volume of the carbon matrix is ≥0.7cm3 / g.
[0065] In some embodiments, the pores in the carbon matrix include micropores with a pore size of less than 2 nm, and the proportion of the micropores is ≥80%. Specifically, the proportion of micropores can be 80%, 82%, 85%, 88%, 90%, 92%, 93%, 95%, 98% or 99%, etc., without limitation here. It can be understood that the size of the silicon particles deposited in the pores of the carbon matrix is determined by the size of the pores. The higher the proportion of micropores, the smaller the average pore size of the pores, and the smaller the silicon particles deposited in the pores. The silicon particles deposited in the pores of the carbon matrix are small, and the volume expansion of the negative electrode material during the cycle is small, which is beneficial to improve the cycle performance of the negative electrode material. Preferably, the proportion of micropores is ≥90%; further preferably, the proportion of micropores is ≥95%.
[0066] In some embodiments, the average pore size of the pores in the carbon matrix is ≤5nm, and can be 0.1nm, 0.5nm, 1nm, 1.5nm, 2nm, 2.5nm, 3nm, 3.5nm, 4nm, 4.5nm or 5nm, etc., and can also be other values within the above range, which are not limited here. Preferably, the average pore size of the pores in the carbon matrix is ≤2nm; more preferably, the average pore size of the pores in the carbon matrix is ≤1.8nm.
[0067] In some embodiments, the porosity of the carbon matrix is 40% to 60%, specifically 40%, 41%, 43%, 45%, 48%, 50%, 52%, 54%, 56%, 58% or 60%, etc., and of course it can also be other values within the above range, which is not limited here.
[0068] In some embodiments, the silicon particles include at least one of silicon, silicon oxide, silicon alloy and silicon-carbon composite. Specifically, silicon can be amorphous silicon, crystalline silicon or a composite of crystalline silicon and amorphous silicon, etc., which is not limited here. Silicon alloy can be silicon-lithium alloy, silicon-magnesium alloy, silicon-nickel alloy, etc., which is not limited here.
[0069] In some embodiments, the average particle size of the silicon particles is 1 nm to 500 nm, specifically 1 nm, 5 nm, 10 nm, 50 nm, 100 nm, 150 nm, 200 nm, 300 nm, 350 nm, 400 nm or 500 nm, etc., and of course, other values within the above range are also possible, which are not limited here. Preferably, the average particle size of the silicon particles is 1 nm to 50 nm; more preferably, the average particle size of the silicon particles is 1 nm to 10 nm.
[0070] In some embodiments, the mass content of silicon in the silicon particles is ≥ 99%. The mass content of silicon in the silicon particles within the above range is conducive to improving the purity of the silicon particles and reducing impurities.
[0071] In some embodiments, the negative electrode material further includes a carbon layer located on at least a portion of the surface of the active material. It can be understood that the carbon layer can act as a buffer layer to reduce the volume expansion effect of the negative electrode material to a certain extent, while enhancing the conductivity of the negative electrode material; the carbon layer can also reduce the direct contact between the active material and the electrolyte, inhibit the excessive growth of the SEI film on the surface of the negative electrode material, stabilize the interface of the negative electrode material, and improve the coulombic efficiency of the negative electrode material.
[0072] In some embodiments, the negative electrode material further includes a carbon layer located on at least a portion of the surface of the active material, and the carbon layer includes at least one of graphite carbon and amorphous carbon.
[0073] In some embodiments, the median particle size D50 of the negative electrode material is ≤10 μm, and can be 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm, etc., and can also be other values within the above range, which is not limited here. It can be understood that controlling the median particle size of the negative electrode material within the above range is conducive to improving the cycle performance of the negative electrode material.
[0074] In some embodiments, the specific surface area of the negative electrode material is ≤5m 2 / g, specifically 0.1m 2 / g, 0.5m 2 / g, 1m 2 / g, 1.5m 2 / g, 2m 2 / g, 2.5m 2 / g, 3m 2 / g, 3.5m 2 / g, 4m 2 / g, 4.5m 2 / g or 5m 2 / g, etc., and of course, it can also be other values within the above range, which is not limited here. Controlling the specific surface area of the negative electrode material within the above range is beneficial to improving the initial efficiency and cycle performance of the lithium battery made of the negative electrode material.
[0075] In a second aspect, the present application provides a method for preparing a negative electrode material, comprising the following steps:
[0076] Step S100, providing a carbon substrate having pores;
[0077] Step S200, using silicon source gas to perform vapor deposition on the porous carbon matrix to obtain an active substance, wherein the negative electrode material includes the active substance, wherein the average pore size of the carbon matrix is D nm, the volume concentration of the silicon source gas is N, the flow rate of the silicon source gas is VL / min, the deposition time of the vapor deposition is th, the deposition temperature of the vapor deposition is T°C, and the deposition relationship is controlled to satisfy: K=(10 3 V 2 ND 3 ) / (t 2 T 1.5 ), 1.1≤K≤6.5.
[0078] The preparation method of the negative electrode material provided in the present application utilizes a vapor deposition process to fully fill silicon particles in the pores of a carbon matrix to prepare the negative electrode material. By controlling the deposition conditions, the deposition of silicon particles on the surface of the carbon matrix can be reduced, and the silicon particles can be effectively filled in the pores of the carbon matrix to increase the capacity of the negative electrode material. At the same time, the size and shape of the silicon particles can be controlled to ensure that the negative electrode material can both alleviate volume expansion and maintain structural stability during the cycle, reduce the collapse of the material structure caused by volume expansion during the lithium insertion and extraction process of the negative electrode material, effectively reduce the occurrence of side reactions, and thus improve the cycle performance of the negative electrode material.
[0079] Step S100, providing a carbon substrate having pores.
[0080] It should be noted that the carbon matrix with pores in the present application can be purchased and used directly, or can be prepared by carbonizing a carbon source, which is not limited here.
[0081] In some embodiments, the step of providing a carbon matrix having pores comprises: carbonizing a carbon source, and then acid-washing and activating the carbonized product to obtain a carbon matrix having pores.
[0082] In some embodiments, the carbon source includes at least one of husks, starch, coconut shells, rice husks, coal, lignin, sugars, thermoplastic polyurethane (TPU), polylactide, polyglycolide, polyaniline, phenolic resin, polyamide, polyacrylonitrile, polychloroprene, polyphosphate, etc.
[0083] In some embodiments, the temperature of the carbonization treatment is 400°C to 1800°C, and can be 400°C, 500°C, 800°C, 1000°C, 1200°C, 1500°C, 1600°C or 1800°C, etc., which is not limited here; the time of the carbonization treatment is 1h to 15h, and can be 1h, 3h, 5h, 8h, 10h, 12h, 13h, 14h or 15h, etc., which is not limited here.
[0084] In some embodiments, the step of acid washing the carbonized product comprises placing the carbonized product in an acid solution with a concentration of 1 mol / L to 20 mol / L for 0.5 h to 20 h.
[0085] In some embodiments, the step of pickling the carbonized product includes: placing the carbonized product in an acid solution with a concentration of 1 mol / L to 20 mol / L for 0.5 h to 20 h, wherein the acid solution includes at least one of hydrochloric acid, nitric acid, sulfuric acid, carbonic acid, acetic acid, benzoic acid, hydrofluoric acid, oxalic acid and phosphoric acid.
[0086] Specifically, the concentration of the acid solution is 1 mol / L, 3 mol / L, 5 mol / L, 6 mol / L, 8 mol / L, 10 mol / L, 12 mol / L, 15 mol / L, 18 mol / L or 20 mol / L, etc., which is not limited here.
[0087] The time for placing the carbonized product in the acid solution can be 0.5h, 0.8h, 1h, 2h, 3h, 5h, 8h, 12h, 15h, 18h or 20h, etc., which is not limited here.
[0088] In some embodiments, the step of activating the carbonized product includes: drying the acid-washed carbonized product and placing it in a mixture of nitrogen and water vapor for activation. It can be understood that acid washing and activation treatment are conducive to the directional deposition of silicon particles into the pores of the carbon matrix during the subsequent silicon deposition process, thereby reducing the deposition of silicon particles on the surface of the carbon matrix.
[0089] In some embodiments, the step of activating the carbonized product comprises: drying the pickled carbonized product and placing it in a mixed gas of nitrogen and water vapor for activation, wherein the volume ratio of the water vapor to the nitrogen is (0.1-20):80. The volume ratio of water vapor to nitrogen can be 0.1:80, 1:80, 2:80, 3:80, 5:80, 8:80, 10:80, 12:80, 15:80, 18:80 or 20:80, etc., which is not limited here.
[0090] In some embodiments, the step of activating the carbonized product includes: drying the carbonized product after acid washing and placing it in a mixed gas of nitrogen and water vapor for activation treatment, the activation treatment temperature is 400°C to 2000°C, and the activation treatment time is 0.5h to 30h.
[0091] Specifically, the temperature of the activation treatment may be 400°C, 500°C, 800°C, 1000°C, 1200°C, 1500°C, 1800°C or 2000°C, etc., which is not limited here. The time of the activation treatment may be 0.5h, 1h, 3h, 5h, 8h, 10h, 12h, 15h, 18h, 24h or 30h, etc., which is not limited here.
[0092] In some embodiments, the carbon matrix includes at least one of hard carbon, soft carbon, graphite, mesocarbon microbeads, activated carbon, porous carbon, mesoporous carbon, and carbon gel.
[0093] In some embodiments, the total pore volume of the carbon matrix is ≥ 0.4 cm 3 / g, specifically 0.4cm 3 / g, 0.5cm 3 / g, 0.8cm 3 / g, 1cm 3 / g, 1.1cm 3 / g, 1.3cm 3 / g, 1.5cm 3 / g or 1.8cm 3 / g, etc., and of course, other values within the above range may also be used, which are not limited here. Preferably, the total pore volume of the carbon matrix is ≥0.5cm 3 / g; further preferably, the total pore volume of the carbon matrix is ≥0.7cm 3 / g.
[0094] In some embodiments, the pores include micropores with a pore size of less than 2 nm, and the proportion of the micropores is ≥ 80%. Specifically, the proportion of micropores can be 80%, 82%, 85%, 88%, 90%, 92%, 93%, 95%, 98% or 99%, etc., without limitation. Preferably, the proportion of micropores is ≥ 90%; more preferably, the proportion of micropores is ≥ 95%.
[0095] In some embodiments, the average pore size of the pores of the carbon matrix is ≤5nm. Specifically, it can be 0.1nm, 0.5nm, 1nm, 1.5nm, 2nm, 2.5nm, 3nm, 3.5nm, 4nm, 4.5nm or 5nm, etc. Of course, it can also be other values within the above range, which are not limited here. Preferably, the average pore size of the pores of the carbon matrix is ≤2nm; more preferably, the average pore size of the pores of the carbon matrix is ≤1.8nm.
[0096] In some embodiments, the porosity of the carbon matrix is 40% to 60%, specifically 40%, 41%, 43%, 45%, 48%, 50%, 52%, 54%, 56%, 58% or 60%, etc., and of course it can also be other values within the above range, which is not limited here.
[0097] Step S200, using silicon source gas to perform vapor deposition on the porous carbon matrix to obtain an active substance, wherein the negative electrode material includes the active substance, wherein the average pore size of the carbon matrix is D nm, the volume concentration of the silicon source gas is N, the flow rate of the silicon source gas is VL / min, the deposition time of the vapor deposition is th, the deposition temperature of the vapor deposition is T°C, and the deposition relationship is controlled to satisfy: K=(10 3 V 2 ND 3 ) / (t 2 T 1.5 ), 1.1≤K≤6.5.
[0098] Specifically, the value of K can be 1.1, 1.24, 1.58, 1.69, 1.86, 2.05, 2.87, 3, 3.12, 3.5, 3.8, 3.97, 4, 4.3, 4.5, 4.8, 5.2, 5.4, 5.7, 6, 6.1, 6.38, 6.4, 6.45, 6.48 or 6.5, etc., which are not limited here. Controlling the K value within the above range is conducive to filling the silicon particles in the pores of the carbon matrix, reducing the generation of surface silicon and large silicon particles, and can control the size of the silicon particles at the micro-nano level, thereby alleviating the volume expansion of the negative electrode material, effectively reducing the occurrence of side reactions, and improving the cycle performance of the negative electrode material.
[0099] In some embodiments, the silicon source gas includes at least one of monosilane, disilane, monochlorosilane, and dichlorosilane.
[0100] In some embodiments, the average particle size of the carbon matrix is 0.5 μm to 20 μm, specifically 0.5 μm, 1 μm, 1.5 μm, 3 μm, 5 μm, 8 μm, 10.5 μm, 12 μm, 15 μm, 16 μm, 18 μm or 20 μm, etc., and of course it can also be other values within the above range, which is not limited here.
[0101] In some embodiments, the average pore size of the carbon matrix is D nm, 0.1≤D≤20, and the average pore size can be 0.1nm, 0.5nm, 1nm, 3nm, 5nm, 6.5nm, 8.7nm, 10nm, 12.3nm, 15nm, 18nm or 20nm, etc., and of course, it can also be other values within the above range, which are not limited here. It can be understood that controlling the average pore size of the carbon matrix within the above range is conducive to controlling the particle size of the silicon particles, reducing the situation where the size of the silicon particles is too large, and is conducive to alleviating the volume expansion of the silicon particles, reducing the probability of pulverization and crushing of the negative electrode material, and thus improving the cycle performance of the negative electrode material.
[0102] In some embodiments, the volume concentration ratio of the silicon source gas is N, 0.01≤N≤0.8, and the volume concentration ratio of the silicon source gas can be 1%, 5%, 10%, 15%, 20%, 30%, 50%, 60%, 70%, 75% or 80%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0103] In some embodiments, the flow rate of the silicon source gas is VL / min, 0.5≤V≤500, specifically 0.5L / min, 1L / min, 5L / min, 10L / min, 50L / min, 100L / min, 150L / min, 200L / min, 300L / min, 400L / min or 500L / min, etc. Of course, it can also be other values within the above range, which is not limited here.
[0104] In some embodiments, the deposition time of the vapor deposition is th, 0.5≤t≤20, and the deposition time can specifically be 0.5h, 1h, 3h, 5h, 6h, 8h, 10h, 12h, 15h, 18h or 20h, etc., which is not limited here.
[0105] In some embodiments, the deposition temperature of the vapor deposition is T°C, 300≤T≤800, and the deposition temperature can be 300°C, 350°C, 400°C, 500°C, 600°C, 650°C, 700°C or 800°C, etc., and of course, it can also be other values within the above range, which is not limited here. It can be understood that controlling the temperature of the vapor deposition within the above range is conducive to controlling the crystal form of the silicon particles, reducing the crystallinity of the silicon particles, reducing the conversion of amorphous silicon to crystalline silicon, and thereby reducing the volume expansion of the negative electrode material and improving the cycle performance of the negative electrode material.
[0106] In some embodiments, the method further includes: performing carbon coating treatment on the active substance to obtain a negative electrode material having a carbon layer on the surface; the carbon coating treatment includes at least one of solid phase carbon coating, liquid phase carbon coating and gas phase carbon coating.
[0107] It can be understood that carbon coating the active material to form a carbon layer on the surface of the active material can, on the one hand, reduce the direct contact between the negative electrode material and the electrolyte, reduce the occurrence of side reactions between the negative electrode material and the electrolyte, and thus improve the electrochemical performance of the negative electrode material; on the other hand, it can also alleviate the mechanical stress caused by the volume expansion of the negative electrode material, improve the structural stability of the negative electrode material, improve the interface stability, and thus improve the cycle performance of the negative electrode material.
[0108] In some embodiments, the carbon coating treatment step specifically includes: heating the active material, introducing a protective gas and a carbon source gas, and thermally cracking the carbon source gas to obtain a negative electrode material having a carbon layer on the surface.
[0109] In some embodiments, the carbon coating treatment step specifically includes: heating the active material, introducing a protective gas and a carbon source gas, and thermally cracking the carbon source gas to obtain a negative electrode material having a carbon layer on the surface, wherein the carbon source gas is a hydrocarbon.
[0110] In some embodiments, the carbon coating treatment step specifically includes: heating the active material, introducing a protective gas and a carbon source gas, and thermally cracking the carbon source gas to obtain a negative electrode material having a carbon layer on the surface, wherein the carbon source gas includes at least one of methane, ethylene, acetylene, propyne, propylene, propane, toluene, benzene, styrene and phenol.
[0111] In some embodiments, the carbon coating treatment step specifically includes: after heating the active material, introducing a protective gas and a carbon source gas, and thermally cracking the carbon source gas to obtain a negative electrode material with a carbon layer on the surface, wherein the thermal cracking temperature is 600°C to 1000°C, and the thermal cracking time is 30min to 24h.
[0112] Specifically, the temperature of thermal cracking can be 600°C, 620°C, 650°C, 680°C, 700°C, 760°C, 870°C, 900°C, 920°C, 950°C, 980°C or 1000°C, etc., which is not limited here. The time of thermal cracking can be 30 min, 1 h, 3 h, 5 h, 8 h, 12 h, 15 h, 18 h, 20 h, 22 h or 24 h, etc., which is not limited here.
[0113] In some embodiments, the carbon coating step specifically includes: carbonizing a mixture obtained by mixing the active substance with a solid carbon source to obtain a negative electrode material having a carbon layer on the surface.
[0114] In some embodiments, the carbon coating step specifically includes: carbonizing the mixture obtained by mixing the active substance with a solid carbon source to obtain a negative electrode material with a carbon layer on the surface, wherein the carbonization temperature is 500°C to 1000°C, and the carbonization time is 30min to 24h.
[0115] Specifically, the temperature of the carbonization treatment can be 500°C, 540°C, 580°C, 600°C, 620°C, 650°C, 680°C, 700°C, 760°C, 870°C, 900°C, 920°C, 950°C, 980°C or 1000°C, etc., which is not limited here. The time of the carbonization treatment can be 30 min, 1 h, 3 h, 5 h, 8 h, 12 h, 15 h, 18 h, 20 h, 22 h or 24 h, etc., which is not limited here.
[0116] In some embodiments, the carbon coating step specifically includes: carbonizing the mixture obtained by mixing the active substance with a solid carbon source to obtain a negative electrode material having a carbon layer on the surface, wherein the solid carbon source includes at least one of sugars, esters, hydrocarbons, organic acids and high molecular polymers.
[0117] In some embodiments, the carbon coating step specifically includes: carbonizing the mixture obtained by mixing the active substance with a solid carbon source to obtain a negative electrode material with a carbon layer on the surface, wherein the solid carbon source includes at least one of polyvinyl chloride, polyvinyl butyral, polyacrylonitrile, polyacrylic acid, polyethylene glycol, polypyrrole, polyaniline, sucrose, glucose, maltose, citric acid, asphalt, furfural resin, epoxy resin and phenolic resin.
[0118] In some embodiments, the carbon coating step specifically includes: carbonizing the mixture obtained by mixing the active substance with a solid carbon source to obtain a negative electrode material having a carbon layer on the surface, wherein the mass ratio of the solid carbon source to the negative electrode material is (1-200):100, specifically 1:100, 2:100, 5:100, 10:100, 50:100, 100:100, 150:100, 180:100 or 200:100, etc., and is not limited here.
[0119] In some embodiments, the carbon coating step specifically includes: carbonizing a mixture obtained by mixing the active substance with a liquid carbon source to obtain a negative electrode material having a carbon coating layer on the surface.
[0120] In some embodiments, the carbon coating step specifically includes: carbonizing the mixture obtained by mixing the active substance with a liquid carbon source to obtain a negative electrode material having a carbon layer on the surface, wherein the mass ratio of the liquid carbon source to the negative electrode material is (1-200):100, specifically 1:100, 2:100, 5:100, 10:100, 50:100, 100:100, 150:100, 180:100 or 200:100, etc., and is not limited here.
[0121] In some embodiments, the carbon coating step specifically includes: carbonizing the mixture obtained by mixing the active substance with a liquid carbon source to obtain a negative electrode material with a carbon layer on the surface, wherein the liquid carbon source includes at least one of n-hexane, toluene, benzene, xylene, methanol, ethanol, propanol, butanol, pentanol, acetone, butanone, 2-pentanone, methyl acetate, ethyl acetate, propyl acetate, butyl acetate and pentyl acetate.
[0122] In some embodiments, the carbon coating step specifically includes: carbonizing the mixture obtained by mixing the active substance with a liquid carbon source to obtain a negative electrode material with a carbon layer on the surface, wherein the carbonization temperature is 600°C to 1200°C, and the carbonization time is 2h to 20h.
[0123] Specifically, the temperature of the carbonization treatment can be 600°C, 620°C, 650°C, 680°C, 700°C, 760°C, 870°C, 900°C, 920°C, 950°C, 980°C, 1000°C, 1020°C, 1080°C, 1100°C, 1160°C or 1200°C, etc., which is not limited here. The time of the carbonization treatment can be 2h, 3h, 5h, 8h, 12h, 15h, 18h, 20h, 22h, 24h, 25h, 26h, 28h or 30h, etc., which is not limited here.
[0124] In some embodiments, the carbon coating process is performed under a protective atmosphere, wherein the protective atmosphere includes at least one of nitrogen, helium, neon, argon, and krypton.
[0125] In some embodiments, the method further includes: shaping, screening and grading the carbon-coated product to obtain a negative electrode material having a carbon layer on the surface, wherein the shaping includes at least one of crushing, grinding, ball milling and gas crushing.
[0126] In a third aspect, the present application provides a lithium-ion battery, wherein the lithium-ion battery comprises the negative electrode material as described in the first aspect or comprises the negative electrode material prepared by the negative electrode material preparation method as described in the second aspect.
[0127] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
[0128] Example
[0129] Example 1
[0130] (1) The fruit shell was carbonized at 500°C for 5 h, and then the carbonized product was pickled with 5 mol / L hydrochloric acid for 4 h. After drying, it was placed in a heat treatment furnace and a mixture of water vapor and nitrogen (volume ratio 1:80) was introduced for activation treatment at a temperature of 800°C for 12 h to obtain a carbon matrix with an average pore size of 2.1 nm.
[0131] (2) The carbon substrate was placed in a chemical vapor deposition (CVD) device, silane was introduced into the CVD device at a rate of 18 L / min, the volume concentration of silane was controlled to be 20%, and then the temperature was raised to 500°C and a vapor deposition reaction was carried out for 4 hours to obtain an active substance.
[0132] (3) The active substance and the phenolic resin were mixed in a mass ratio of 50:15, and then the mixed material was placed in a high-temperature box furnace, nitrogen was introduced, and heat-treated at 720° C. for 2 h.
[0133] (4) The obtained sample is crushed, sieved, and then classified to obtain a negative electrode material having a carbon layer on the surface.
[0134] The negative electrode material prepared in this embodiment includes an active material, the active material includes a carbon matrix and silicon particles, the carbon matrix has pores, at least part of the silicon particles are distributed in the pores of the carbon matrix, wherein the carbon matrix is porous carbon, the average particle size of the silicon particles is 2.3nm, and the specific surface area of the negative electrode material is 2.9m 2 / g, and the median particle size of the negative electrode material is 10μm.
[0135] The K value of the vapor deposition in this embodiment is 3.35.
[0136] Figure 2 This is a scanning electron microscope (SEM) image of the negative electrode material prepared in Example 1 of the present application.
[0137] Figure 3 The XRD pattern of the negative electrode material prepared in Example 1 of the present application is as follows: Figure 3 As shown, the silicon particles in the negative electrode material are amorphous.
[0138] Figure 4 This is the first charge and discharge curve of the negative electrode material prepared in Example 1 of the present application, such as Figure 4 As shown, the first charge and discharge capacity of the negative electrode material is 1955 mAh / g, and the first efficiency is 92.9%.
[0139] Figure 5 The cycle performance curve of the negative electrode material prepared in Example 1 of the present application is as follows: Figure 5 As shown, the negative electrode material has excellent cycle performance, and the capacity retention rate after 50 cycles is 92.6%.
[0140] Example 2
[0141] (1) A commercial carbon substrate with an average pore size of 1.6 nm was placed in a chemical vapor deposition (CVD) device, silane was introduced into the CVD device at a rate of 19 L / min, and the volume concentration of silane was controlled to be 40%. The temperature was then raised to 600°C and a vapor deposition reaction was performed for 3 hours to obtain an active substance.
[0142] (2) The active substance and sucrose were mixed in a mass ratio of 50:45, and then the mixed material was placed in a high-temperature box furnace, nitrogen was introduced, and heat-treated at 620° C. for 2 h.
[0143] (3) The obtained sample is crushed, sieved, and then classified to obtain a negative electrode material having a carbon layer on the surface.
[0144] The negative electrode material prepared in this embodiment includes an active material, the active material includes a carbon matrix and silicon particles, the carbon matrix has pores, at least part of the silicon particles are distributed in the pores of the carbon matrix, wherein the carbon matrix is porous carbon, the average particle size of the silicon particles is 1.8 nm, and the specific surface area of the negative electrode material is 3.4 m 2 / g, and the median particle size of the negative electrode material is 8.2μm.
[0145] The K value of the vapor deposition in this embodiment is 4.47.
[0146] Example 3
[0147] (1) The starch was carbonized at 600°C for 8 h, and then the carbonized product was pickled with 3 mol / L hydrochloric acid for 7 h. After drying, it was placed in a heat treatment furnace and a mixture of water vapor and nitrogen (volume ratio 3:80) was introduced for activation treatment at 900°C for 12 h to obtain a carbon matrix with an average pore size of 1.8 nm.
[0148] (2) The carbon substrate was placed in a chemical vapor deposition (CVD) device, silane was introduced into the CVD device at a rate of 16 L / min, the volume concentration of silane was controlled to be 25%, and then the temperature was raised to 700°C, and a vapor deposition reaction was carried out for 2.5 hours to obtain an active substance.
[0149] (3) The active substance and the epoxy resin were mixed in a mass ratio of 50:55, and then the mixed material was placed in a high-temperature box furnace, nitrogen was introduced, and heat-treated at 650° C. for 2 h.
[0150] (4) The obtained sample is crushed, sieved, and then classified to obtain a negative electrode material having a carbon layer on the surface.
[0151] The negative electrode material prepared in this embodiment includes an active material, the active material includes a carbon matrix and silicon particles, the carbon matrix has pores, at least part of the silicon particles are distributed in the pores of the carbon matrix, wherein the carbon matrix is porous carbon, the average particle size of the silicon particles is 2.0 nm, and the specific surface area of the negative electrode material is 3.8 m 2 / g, and the median particle size of the negative electrode material is 5.9μm.
[0152] The K value of the vapor deposition in this embodiment is 3.22.
[0153] Example 4
[0154] (1) A commercial carbon substrate with an average pore size of 1.3 nm was placed in a chemical vapor deposition (CVD) device, and silane was introduced into the CVD device at a rate of 21 L / min, and the volume concentration of silane was controlled to be 50%. The temperature was then raised to 500°C and a vapor deposition reaction was performed for 4 hours to obtain an active substance.
[0155] (2) The active substance and the phenolic resin were mixed in a mass ratio of 30:45, and then the mixed material was placed in a high-temperature box furnace, nitrogen was introduced, and heat-treated at 820° C. for 4 h.
[0156] (3) The obtained sample is crushed, sieved, and then classified to obtain a negative electrode material having a carbon layer on the surface.
[0157] The negative electrode material prepared in this embodiment includes an active material, the active material includes a carbon matrix and silicon particles, the carbon matrix has pores, at least part of the silicon particles are distributed in the pores of the carbon matrix, wherein the carbon matrix is porous carbon, the average particle size of the silicon particles is 1.6 nm, and the specific surface area of the negative electrode material is 2.4 m 2 / g, and the median particle size of the negative electrode material is 7.4μm.
[0158] The K value of vapor deposition in this embodiment is 2.71.
[0159] Example 5
[0160] The difference from Example 4 is:
[0161] (1) A commercial carbon substrate with an average pore size of 1.3 nm was placed in a chemical vapor deposition (CVD) device, and silane was introduced into the CVD device at a rate of 21 L / min, and the volume concentration of silane was controlled to be 80%. The temperature was then raised to 500°C and a vapor deposition reaction was performed for 4 hours to obtain an active substance.
[0162] The negative electrode material prepared in this embodiment includes an active material, the active material includes a carbon matrix and silicon particles, the carbon matrix has pores, at least part of the silicon particles are distributed in the pores of the carbon matrix, wherein the carbon matrix is porous carbon, the average particle size of the silicon particles is 3.5 nm, and the specific surface area of the negative electrode material is 2.1 m 2 / g, and the median particle size of the negative electrode material is 8.2μm.
[0163] The K value of the vapor deposition in this embodiment is 4.3.
[0164] Example 6
[0165] The difference from Example 4 is:
[0166] (1) A commercial carbon substrate with an average pore size of 1.3 nm was placed in a chemical vapor deposition (CVD) device, silane was introduced into the CVD device at a rate of 100 L / min, and the volume concentration of silane was controlled to be 5%. The temperature was then raised to 500°C and a vapor deposition reaction was performed for 6 hours to obtain an active substance.
[0167] The negative electrode material prepared in this embodiment includes an active material, the active material includes a carbon matrix and silicon particles, the carbon matrix has pores, at least part of the silicon particles are distributed in the pores of the carbon matrix, wherein the carbon matrix is porous carbon, the average particle size of the silicon particles is 3.5 nm, and the specific surface area of the negative electrode material is 2.1 m 2 / g, and the median particle size of the negative electrode material is 8.2μm.
[0168] The K value of the vapor deposition in this embodiment is 2.73.
[0169] Example 7
[0170] The difference from Example 1 is:
[0171] (2) The carbon substrate was placed in a chemical vapor deposition (CVD) device, silane was introduced into the CVD device at a rate of 18 L / min, the volume concentration of silane was controlled to be 20%, and then the temperature was raised to 800°C and a vapor deposition reaction was carried out for 4 hours to obtain an active substance.
[0172] The negative electrode material prepared in this embodiment includes an active material, the active material includes a carbon matrix and silicon particles, the carbon matrix has pores, at least part of the silicon particles are distributed in the pores of the carbon matrix, wherein the carbon matrix is porous carbon, the average particle size of the silicon particles is 5.5nm, and the specific surface area of the negative electrode material is 2.8m 2 / g, and the median particle size of the negative electrode material is 9.8μm.
[0173] The K value of the vapor deposition in this embodiment is 1.66.
[0174] Example 8
[0175] The difference from Example 1 is:
[0176] (2) The carbon substrate was placed in a chemical vapor deposition (CVD) device, silane was introduced into the CVD device at a rate of 18 L / min, the volume concentration of silane was controlled to be 20%, and then the temperature was raised to 600°C and a vapor deposition reaction was carried out for 6 hours to obtain an active substance.
[0177] The negative electrode material prepared in this embodiment includes an active material, the active material includes a carbon matrix and silicon particles, the carbon matrix has pores, at least part of the silicon particles are distributed in the pores of the carbon matrix, wherein the carbon matrix is porous carbon, the average particle size of the silicon particles is 5.5nm, and the specific surface area of the negative electrode material is 2.8m 2 / g, and the median particle size of the negative electrode material is 9.8μm.
[0178] The K value of the vapor deposition in this embodiment is 1.1.
[0179] Comparative Example 1
[0180] The difference from Example 1 is:
[0181] (2) The carbon substrate was placed in a chemical vapor deposition (CVD) device, silane was introduced into the CVD device at a rate of 34 L / min, the volume concentration of silane was controlled to be 22%, and then the temperature was raised to 500°C and a vapor deposition reaction was carried out for 4 hours to obtain an active substance.
[0182] The negative electrode material prepared in this comparative example includes an active material, the active material includes a carbon matrix and silicon particles, the carbon matrix has pores, at least part of the silicon particles are distributed in the pores of the carbon matrix, wherein the carbon matrix is porous carbon, the average particle size of the silicon particles is 2.3 nm, and the specific surface area of the negative electrode material is 3.1 m 2 / g, and the median particle size of the negative electrode material is 9.7μm.
[0183] The K value of the vapor deposition in this embodiment is 13.16.
[0184] Comparative Example 2
[0185] The difference from Example 1 is:
[0186] (1) The fruit shell was carbonized at 500°C for 5 h, and then the carbonized product was pickled with 5 mol / L hydrochloric acid for 4 h. After drying, it was placed in a heat treatment furnace and a mixture of water vapor and nitrogen (volume ratio 5:80) was introduced for activation treatment at a temperature of 1500°C for 12 h to obtain a carbon matrix with an average pore size of 4.5 nm.
[0187] The negative electrode material prepared in this comparative example includes an active material, the active material includes a carbon matrix and silicon particles, the carbon matrix has pores, at least part of the silicon particles are distributed in the pores of the carbon matrix, wherein the carbon matrix is porous carbon, the average particle size of the silicon particles is 4.9 nm, and the specific surface area of the negative electrode material is 2.9 m 2 / g, and the median particle size of the negative electrode material is 10.3μm.
[0188] The K value of the vapor deposition in this embodiment is 33.
[0189] Comparative Example 3
[0190] The difference from Example 1 is:
[0191] (2) The carbon substrate was placed in a chemical vapor deposition (CVD) device, silane was introduced into the CVD device at a rate of 18 L / min, the volume concentration of silane was controlled to be 20%, and then the temperature was raised to 900°C and a vapor deposition reaction was carried out for 5 hours to obtain an active substance.
[0192] The negative electrode material prepared in this comparative example includes an active material, the active material includes a carbon matrix and silicon particles, the carbon matrix has pores, at least part of the silicon particles are distributed in the pores of the carbon matrix, wherein the carbon matrix is porous carbon, the average particle size of the silicon particles is 2.4 nm, and the specific surface area of the negative electrode material is 3.3 m 2 / g, and the median particle size of the negative electrode material is 9.8μm.
[0193] The K value of the vapor deposition in this embodiment is 0.89.
[0194] Test method:
[0195] (1) Testing method for specific surface area of negative electrode materials:
[0196] The specific surface area was measured using the American Micromeritics TriStar 3000 specific surface area and pore size analyzer.
[0197] (2) Testing method for total pore volume of negative electrode material or carbon matrix:
[0198] The test was carried out using the ASAP2460 equipment from Micromeritics, USA. The pore volume V was calculated using the BJH Desorption cumulative volume of pores model. Calculated within the pore size range.
[0199] Micromeretics ASAP 2460 was used for micropore and mesopore analysis. At liquid nitrogen temperature, the equilibrium adsorption of nitrogen on the surface of an object is related to its pore size and other characteristics. Combined with the law of the change of adsorption amount with relative pressure during adsorption, multiple models can be fitted to calculate the pore size. The report generated by the software uses density functional theory (abbreviated as DFT) method to calculate the pore size distribution, total pore volume and pore volume within a certain range.
[0200] (3) Pore size test method of negative electrode material or carbon matrix:
[0201] Take an appropriate amount of sample particles and measure the pore size and porosity under a transmission electron microscope (TEM).
[0202] (4) Testing method of silicon particle size:
[0203] The nano-silicon particles are observed by a field emission scanning electron microscope or a transmission electron microscope, and the particle sizes of 5-10 nano-silicon particles are directly measured by a scale, and the average value of the particle sizes is taken as the final particle size of the nano-silicon particles.
[0204] (5) Test method for particle size of negative electrode material:
[0205] Malvern Laser Particle Sizer MS3000 is used. Based on the principle that the intensity distribution of scattered light generated by particles in all directions depends on the size of the particles, large particles have small scattering angles and small particles have large scattering angles, the particle size distribution of the particles can be obtained by using the scattered light intensity distribution of laser diffraction.
[0206] (6) Electrochemical performance test:
[0207] The following method was used to test the electrochemical cycle performance: the negative electrode materials, conductive agents and binders prepared in Examples 1 to 8 and Comparative Examples 1 to 3 were dissolved in a solvent in a mass percentage of 94:1:5, and the solid content was controlled to be 50%, and then coated on a copper foil current collector, vacuum dried, and the negative electrode plate was obtained; then the ternary positive electrode plate prepared by the traditional mature process, 1 mol / L lithium hexafluorophosphate LiPF6 / (ethylene carbonate EC+dimethyl carbonate DMC+ethyl methyl carbonate EMC) (v / v=1:1:1) electrolyte, Celgard2400 diaphragm, and shell were assembled into 18650 cylindrical single cells using conventional production processes. The charge and discharge test of the cylindrical battery was carried out on the LAND battery test system of Wuhan Jinnuo Electronics Co., Ltd. at room temperature, 0.2C constant current charge and discharge, and the charge and discharge voltage was limited to 2.75~4.2V. The first reversible capacity, first cycle charge capacity and first cycle discharge capacity were obtained. The first coulomb efficiency = first cycle discharge capacity / first cycle charge capacity.
[0208] The cycle was repeated for 50 times. The thickness of the electrode of the lithium-ion battery was measured with a micrometer and found to be H1. The expansion rate after 50 cycles = (H1-H0) / H0×100%.
[0209] Repeat the cycle for 50 cycles and record the discharge capacity as the remaining capacity of the lithium-ion battery; capacity retention rate = remaining capacity / initial capacity*100%.
[0210] The test results are shown in Table 1.
[0211] Table 1 Performance test results of negative electrode materials in various embodiments and comparative examples
[0212]
[0213] According to the data in Table 1, the negative electrode materials prepared in Examples 1 to 8 are prepared by fully filling the silicon particles in the pores of the carbon matrix using a vapor deposition process. By controlling the deposition conditions, the deposition of silicon particles on the surface of the carbon matrix can be reduced, and the silicon particles are effectively filled in the pores of the carbon matrix to increase the capacity of the negative electrode material. At the same time, the size and morphology of the silicon particles can be controlled to ensure that the negative electrode material can both alleviate volume expansion and maintain structural stability during the cycle, reduce the collapse of the material structure caused by volume expansion during the lithium insertion and extraction process of the negative electrode material, and effectively reduce the occurrence of side reactions between the negative electrode material and the electrolyte, thereby improving the cycle performance of the negative electrode material.
[0214] According to the test data of Example 1 and Comparative Example 1 in Table 1, during the preparation process of the negative electrode material of Comparative Example 1, the flow rate V of silane introduced during the vapor deposition process is too large, and the silane gas load introduced at the same time increases, resulting in an increase in the deposition amount of silicon particles in the pores of the carbon matrix, and the silicon particles are easy to grow, which eventually makes the particle size of the silicon particles in the pores of the carbon matrix too large, and the B value of the negative electrode material increases, and B / A deviates from the above range. During the cycle process, due to the excessive particle size of the silicon particles, the volume expansion of the negative electrode material is significantly increased, which in turn causes the material to be pulverized and broken, resulting in the intensification of the side reaction between the negative electrode material and the electrolyte, thereby causing the capacity decay of the negative electrode material, the first coulomb efficiency and the cycle performance to decrease.
[0215] According to the test data of Example 1 and Comparative Example 2 in Table 1, it can be known that during the preparation process of the negative electrode material of Comparative Example 2, the average pore size of the porous carbon material is too large, resulting in the excessive particle size of the silicon particles deposited in the pores of the carbon matrix, the B value of the negative electrode material increases, and B / A deviates from the above range. During the cycle process, due to the excessive particle size of the silicon particles, the volume expansion of the negative electrode material is significantly increased, which in turn causes the material to be pulverized and broken, resulting in the intensification of the side reaction between the negative electrode material and the electrolyte, thereby causing the capacity decay of the negative electrode material, the first coulomb efficiency and the cycle performance to decrease.
[0216] According to the test data of Example 1 and Comparative Example 3 in Table 1, it can be known that during the preparation process of the negative electrode material of Comparative Example 3, the temperature of vapor deposition is too high, the silicon-based material is prone to secondary growth, and a larger silicon size is generated. Moreover, at high temperature, the silicon-based material will be transformed from amorphous silicon to crystalline silicon, and the lithium insertion peak of the crystalline silicon will be enhanced, that is, the peak value of the negative electrode material at A will be enhanced, but at the same time, the peak value of the negative electrode material at B will be stronger, the value of B / A increases, B / A deviates from the above range, the volume expansion of the negative electrode material increases, and it is easy to cause pulverization and breakage of the material, aggravating the side reaction between the material and the electrolyte, and then leading to the capacity decay of the material, the first coulomb efficiency and the cycle performance decrease.
Claims
1. A negative electrode material, characterized in that: The active material comprises a carbon matrix and silicon particles, wherein the carbon matrix has pores, and at least part of the silicon particles are distributed in the pores of the carbon matrix; A three-electrode battery consisting of a negative electrode prepared from the negative electrode material as a working electrode, metal lithium as a reference electrode, metal lithium as a counter electrode and an electrolyte containing metal lithium ions is charged and discharged to obtain a curve graph showing the relationship between the differential value dQ / dV obtained by differentiating the charge and discharge capacity Q of the potential V of the working electrode with respect to the reference electrode and the potential V of the working electrode; In the curve diagram of the relationship between dQ / dV and potential V, when the negative electrode material is energized in the direction of delithiation, the differential value dQ / dV of the potential V between 20mV and 80mV has a maximum peak value A, the differential value dQ / dV of the potential V between 120mV and 210mV has a maximum peak value B, and B / A≤4.
2. The negative electrode material according to claim 1, characterized in that It meets at least one of the following technical features: (1) The carbon matrix comprises at least one of hard carbon, soft carbon, graphite, mesophase carbon microbeads, activated carbon, porous carbon, mesoporous carbon or carbon gel; (2) The total pore volume of the carbon matrix is ≥ 0.4 cm 3 / g; (3) The pores in the carbon matrix include micropores, and the volume proportion of the micropores in the total pore volume is ≥ 80%; (4) The average pore size of the pores in the carbon matrix is ≤5 nm; (5) The porosity of the carbon matrix is 40% to 60%; (6) The silicon particles include at least one of elemental silicon, silicon oxide, silicon alloy and silicon-carbon composite; (7) The average particle size of the silicon particles is 1 nm to 500 nm; (8) The mass content of silicon in the silicon particles is ≥ 99%.
3. The negative electrode material according to claim 1 or 2, characterized in that: The active material further comprises a carbon layer located on at least a portion of the surface of the active material, which satisfies at least one of the following technical features: (1) The carbon layer includes at least one of graphite carbon and amorphous carbon; (2) The median particle size D of the negative electrode material 50 ≤10μm; (3) The specific surface area of the negative electrode material is ≤5m 2 / g; (4) The total pore volume of the negative electrode material is 0.001 cm 3 / g~0.1cm 3 / g.
4. A method for preparing a negative electrode material, characterized in that: The steps include: providing a carbon matrix having pores; The carbon matrix with pores is subjected to vapor deposition using a silicon source gas to obtain an active substance, wherein the negative electrode material includes the active substance, wherein the average pore size of the carbon matrix is D nm, the volume concentration of the silicon source gas is N, the flow rate of the silicon source gas is VL / min, the deposition time of the vapor deposition is th, the deposition temperature of the vapor deposition is T°C, and the deposition relationship is controlled to satisfy: K=(10 3 V 2 ND 3 ) / (t 2 T 1.5 ), 1.1≤K≤6.
5.
5. The preparation method according to claim 4, characterized in that: It meets at least one of the following technical features: (1) The silicon source gas includes at least one of monosilane, disilane, monochlorosilane and dichlorosilane; (2) The average pore size of the carbon matrix is 0.1 nm to 20 nm; (3) The volume concentration of the silicon source gas is 1% to 80%; (4) The flow rate of the silicon source gas is 0.5 L / min to 500 L / min; (5) The deposition time of the vapor deposition is 0.5h to 20h; (6) The deposition temperature of the vapor deposition is 300°C to 800°C.
6. The preparation method according to claim 4, characterized in that: It meets at least one of the following technical features: (1) The carbon matrix comprises at least one of hard carbon, soft carbon, graphite, mesophase carbon microbeads, activated carbon, porous carbon, mesoporous carbon or carbon gel; (2) The total pore volume of the carbon matrix is ≥ 0.4 cm 3 / g; (3) The pores in the carbon matrix include micropores, and the proportion of the micropores is ≥ 80%; (4) The average pore size of the pores in the carbon matrix is ≤5 nm; (5) The porosity of the carbon matrix is 40% to 60%.
7. The preparation method according to claim 4, characterized in that: The step of providing a carbon matrix with pores comprises: carbonizing a carbon source, and then acid-washing and activating the carbonized product to obtain a carbon matrix with pores.
8. The preparation method according to claim 7, characterized in that: It meets at least one of the following technical features: (1) The carbon source comprises at least one of fruit shell, starch, coconut shell, rice husk, coal, lignin, sugar, thermoplastic polyurethane, polylactide, polyglycolide, polyaniline, phenolic resin, polyamide, polyacrylonitrile, polychloroprene, polyphosphate, etc.; (2) The temperature of the carbonization treatment is 400° C. to 1800° C., and the time of the carbonization treatment is 1 h to 15 h; (3) the step of acid washing the carbonized product comprises: placing the carbonized product in an acid solution with a concentration of 1 mol / L to 20 mol / L for 0.5 h to 20 h; (4) the step of acid washing the carbonized product comprises: placing the carbonized product in an acid solution with a concentration of 1 mol / L to 20 mol / L for 0.5 h to 20 h, wherein the acid solution comprises at least one of hydrochloric acid, nitric acid, sulfuric acid, carbonic acid, acetic acid, benzoic acid, hydrofluoric acid, oxalic acid and phosphoric acid; (5) the step of activating the carbonized product comprises: drying the acid-washed carbonized product and placing it in a mixed gas of nitrogen and water vapor for activation; (6) The step of activating the carbonized product comprises: drying the carbonized product after acid washing and placing it in a mixed gas of nitrogen and water vapor for activation treatment, wherein the volume ratio of the water vapor to the nitrogen is (0.1-20):80; (7) The step of activating the carbonized product comprises: drying the carbonized product after acid washing and placing it in a mixed gas of nitrogen and water vapor for activation treatment, wherein the temperature of the activation treatment is 400° C. to 2000° C. and the time of the activation treatment is 0.5 h to 30 h.
9. The preparation method according to claim 5, characterized in that: The method further comprises: The active material is subjected to carbon coating treatment to obtain a negative electrode material having a carbon layer on the surface; the carbon coating treatment includes at least one of solid phase carbon coating, liquid phase carbon coating and gas phase carbon coating.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode material according to any one of claims 1 to 3 or comprises the negative electrode material prepared by the negative electrode material preparation method according to any one of claims 4 to 9.
Citation Information
Cited By
Negative electrode material and preparation method therefor, lithium-ion battery
EP4579804A1
Negative electrode material and preparation method therefor, lithium-ion battery
WO2025091988A1